2020
DOI: 10.1007/s00381-020-04946-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study across pediatric central nervous system tumors implicates shared predisposition and points to 1q25.2 (PAPPA2) and 11p12 (LRRC4C) as novel candidate susceptibility loci

Abstract: Introduction Central nervous system (CNS) tumors constitute the most common form of solid neoplasms in children, but knowledge on genetic predisposition is sparse. In particular, whether susceptibility attributable to common variants is shared across CNS tumor types in children has not been investigated. The purpose of this study was to explore potential common genetic risk variants exhibiting pleiotropic effects across pediatric CNS tumors. We also investigated whether such susceptibility differs between earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…SFMBT2 , a circRNA located on chromosome 10p14, had an increased expression level in gastric cancer tissues and was associated with the proliferation of gastric cancer cells [ 34 ]. LRRC4C (chromosome 11p12) was a novel candidate susceptibility gene for pediatric central nervous system tumors [ 35 ]. NELL1 (chromosome 11p15.1) was associated with bone formation and osteoclast differentiation [ 36 ], and ANO5 (chromosome 11p15.1) was related to myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…SFMBT2 , a circRNA located on chromosome 10p14, had an increased expression level in gastric cancer tissues and was associated with the proliferation of gastric cancer cells [ 34 ]. LRRC4C (chromosome 11p12) was a novel candidate susceptibility gene for pediatric central nervous system tumors [ 35 ]. NELL1 (chromosome 11p15.1) was associated with bone formation and osteoclast differentiation [ 36 ], and ANO5 (chromosome 11p15.1) was related to myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to plays an important role in neural development and malignant transformation of glioma, and has been identified as a tumour suppressor gene for glioma 14 . Especially in recent years, there have been experiments to prove that LRRC4 is involved in nasopharyngeal carcinoma, pituitary adenoma and epithelial ovarian cancer 15 , 40 , 41 , and more importantly, a certain common germline variant in LRRC4C has been implicated in confer increased risk of developing tumors in the central nervous system during childhood 42 . Combined with our results, we have more reason to believe that LRRC4C is involved in the tumour progression of colon cancer and gastric cancer in a similar way to LRRC4.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified novel cancer susceptibility loci for some pediatric cancer types [1][2][3][4]. However, in GWAS studies, the research participants are typically unrelated, and rare variants are not easily identified due to a lack of statistical power [5,6].…”
Section: Introductionmentioning
confidence: 99%